Prevention of human exposure to livestock faecal waste in the household: a scoping study of interventions conducted in sub-Saharan Africa - Sentamu, Derrick N.; Kungu, J.; Dione, Michel M.; Thomas, Lian F. (Springer, 2023)
Background Poorly managed animal faecal waste can result in detrimental environmental and public health implications. Limiting human exposure to animal waste through Animal inclusive Water Sanitation and Hygiene (A-WASH) strategies is imperative to improve public health in livestock keeping households but has received little attention to date. A small number of A-WASH interventions have previously been identified through a systematic review by another research team, and published in 2017. To inform intervention design with the most up-to-date information, a scoping study was conducted to map the existing evidence for A-WASH in sub-Saharan Africa (SSA) emerging since the previous review.